Civic self-determination : the approach to defence funding - Navaitis, Gediminas; Labutis, Gintaras; Povilaitienė, Neringa (Social Welfare: Interdisciplinary Approach, 2014)
Researches on levels of happiness enable to comprehensively analyse information about the society, political culture and public spirit. One of the fields of such researches can be the research on the relation between the level of happiness of the society and governance of the state. Responding to this field, the public opinion research centre “Vilmorus” conducted a representative survey of Lithuanian population, aiming to find out respondents’ opinions about the level of happiness last year and during next five years’ period as well as their attitude to that part of public expenditure which, seeking the increase of residents’ level of happiness, should be allocated for defence of the state. In total, 1005 respondents were surveyed (people over 18 years old from 19 towns and 31 villages). The research also revealed that the level of happiness determined respondents’ opinions about distribution of state budget and funding of defence of the state. It was found that in the opinion of respondents with lower level of happiness there was no need to allocate funds for defence of the state at all.
Keywords: level of happiness of the Lithuanian society; public spirit; approach to funding of defence of the state